Dormancy and Changes in Phenolic Compounds of Artemesia Scoparia Seeds - Al-Charchafchi, Fawzia; J, Fawzia M; Kamel, Widad M (Annals of Arid Zone, 2016)
Poor germination of fresh seeds of Arttmesio scoporia (30% in husked and 5% in unhusked seeds) was found to be due to the relatively high percentage of phenolic constituents of the seeds (9.75) and their bracts (6.50). After one year of dry storage, when the total phenolic compounds decreased to 1.45% in seeds and 3.95% in bracts, the germination of both husked and unhusked seeds improved to 98% and 30%, respectively.